Bahasa Gaul “Jaksel” Sebagai Eksistensi Di Kalangan Remaja Jakarta - Haura Asqo Balqis; Sheryl Delvina Aurora Anggoro; Aniek Irawatie (Universitas Persada Indonesia YAI, 2023)
Language is used as a means of communication between individuals with each other, both orally and in writing. Thealteration causes an increase in the type of language over time and gives rise to many new languages. As of now, thereis a dominant language in society, namely slang. Slang itself has existed for a long time, known as program language.Slang is a non-standard language, this language is usually used by teenagers when they communicate. One exampleof this slang is the slang